The and terms of an arithmetic progression are and , respectively. Find the sum of the first terms of this progression.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Relevant wiki: Arithmetic Progressions
The n t h term of an arithmetic progression is given by a n = a m + ( n − m ) d where d is the common difference. Using this formula to solve for d , we have
3 8 9 = 1 8 1 + ( 3 0 − 1 4 ) d ⟹ d = 1 3
Using this formula again to solve for a 1 , we have
a 1 = a 1 4 + ( 1 − 1 4 ) d = 1 8 1 − 1 3 ( 1 3 ) = 1 2
The sum of the terms of an arithmetic progression is given by s = 2 n [ 2 a 1 + ( n − 1 ) d ] , we have
s 2 5 = 2 2 5 [ 2 ( 1 2 ) + 2 4 ( 1 3 ) ] = 4 2 0 0